Epidemiological investigation of factors influencing suicide in Zahedan - Hossein Izadirad; Mehdi Zanganeh Baygi; Fereshteh Naroei; Parisa Mohammadimi (Payesh)
Objective(s): Suicide and attempted suicide are an important issue of public health and antisocial behavior. In addition to personal and family losses, the phenomenon is also considered a social loss. According to the cultural context of Sistan and Baluchistan province, the present study was conducted with the aim of epidemiological investigation of factors influencing suicide in Zahedan. Methods: The present was a cross-sectional study that conducted on all suicide cases from March 21,2019 to March 20, 2023 in Zahedan covered by hospitals affiliated with Zahedan University of Medical Sciences. The data was collected by census and using the Ministry of Health registry. Data analysis was done using SPSS-v22 and descriptive and analytical tests. Results: According to the results, 3304 people (94.6%) attempted suicide and 187 people (5.3%) had complete suicide. The highest number of complete suicides was 67 people (35.8 percent) and 1370 suicide attempts (41.5 percent) related to the age group of 10 to 20 years. According to the chi-square test, a significant relationship was observed between sex, age group, marital status, education level and place of residence with suicide (P<0.05). So that the highest number of suicides was in the age group of 10 to 20 years 1437 people (41.1%), women 2212 people (63.3%), single status 1413 people (40.4%), high school education level 1131 people (32.4%) and 2775 people (79.5%) with urban residence. The most common method of suicide was drug use in 2845 cases (81.4%) and substance use in 193 cases (5.5%). Conclusion: In general, various demographic and environmental factors such as gender, age group, education level, place of residence, marital status and access to drugs and drugs might increase the risk of suicide. Considering the cultural context of the region, it is necessary to take more serious decisions to prevent suicide in vulnerable groups of teenagers, women and never married individuals. Also, the necessary planning to reduce access to some drugs and narcotics should be considered by the officials.